OC-066 The Cancer Research UK (Cruk) Funded ICGC Oesophageal Adenocarcinoma Project: MRC Research Centre and Cruk Cambridge Research Institute. (4th June 2013) - Weaver, JMJ; Shannon, N; Ross-Innes, C; Lynch, A; Forshew, T; Barbera, M; Ong, C-A; Lao-Sirieix, P; Dunning, M; Smith, L; Smith, M; Carvalho, B; et al.
Abstract : Introduction: Esophageal adenocarcinoma (EAC) has one of the fastest rising incidences of any cancer in the western world. With a 5-year survival below 10% it is one of the most common causes of cancer death in US and UK. Currently little is understood about the genetic alterations that drive the development of OAC. Better understanding of these alterations may allow the development of novel therepeutic approaches Methods: We have performed whole genome sequencing on 22 cases. Targeted amplicon resequencing of 27 recurrently mutated genes was performed on a validation cohort of 100 further oesophageal adenocarcinomas. Results: In the discover set of 22 OACs we identified recurrent mutations (>3 tumours) in 31 genes including several implicated in tumorigenesis; TP53, CDKN2A, ARID1A. Strikingly in the validation cohort we observed that > 30% of EAC samples harbour mutation of one or both of the SWI/SNF complex members ARID1A and SMARCA4. In addition we identified highly recurrent mutations in several additional genes including TRIM58, SSTR4 and MYO18B. Conclusion: Whole genome sequencing provides an unbiased screen of mutational architecture of OAC. This has allowed the identification of several recurrently mutated genes not previously implicated in this disease providing a unique insight to it's pathogenesis Disclosure of Interest: None Declared